2016
DOI: 10.1002/hyp.10855
|View full text |Cite
|
Sign up to set email alerts
|

The June 2013 Alberta catastrophic flooding event – part 2: fine‐scale precipitation and associated features

Abstract: Data obtained from a variety of sources including, the Canadian Lightning Detection Network, weather radars, weather stations and operational numerical weather model analyses were used to address the evolution of precipitation during the June 2013 southern Alberta flood. The event was linked to a mid-level closed low pressure system to the west of the region and a surface low pressure region initially to its south. This configuration brought warm, moist unstable air into the region that led to dramatic, organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…A more detailed analysis of the precipitation and radar observations for the J13 event is given in Kochtubajda et al (2016), who found a coupling between warm-rain collision coalescence processes and ice processes during the night before the flooding, as well as a high frequency of lightning and the presence of hail.…”
Section: B Comparison Between Simulated and Observed Precipitation Smentioning
confidence: 99%
See 1 more Smart Citation
“…A more detailed analysis of the precipitation and radar observations for the J13 event is given in Kochtubajda et al (2016), who found a coupling between warm-rain collision coalescence processes and ice processes during the night before the flooding, as well as a high frequency of lightning and the presence of hail.…”
Section: B Comparison Between Simulated and Observed Precipitation Smentioning
confidence: 99%
“…Regional water budget assessments and air parcel back-trajectory analyses are carried out to examine the sources and transport of the remote moisture for the J13 storm. This article is a follow-up to two companion papers that discuss the synoptic and observational aspects of the J13 storm (Liu et al 2016;Kochtubajda et al 2016).…”
Section: Introductionmentioning
confidence: 96%
“…Over 100 mm of rainfall fell in the area southeast of Jasper; the area extending south of Sundre towards Pincher Creek received more than 200 mm and the station at Burns Creek measured over 300 mm. More detailed analysis of the precipitation features associated with this event can be found in Part 2 of this study (this volume, Kochtubajda et al, 2016).…”
Section: A Climatological View Of the 19-21 June 2013 Precipitation Ementioning
confidence: 99%
“…Milrad et al (2015) studied the 2013 Alberta flooding with a focus on antecedent large-scale atmospheric flow patterns and synoptic-scale dynamic characteristics. Li et al (2016) employed the Weather Research and Forecast (WRF) model to numerically investigate dynamic features that led to the heavy rainfall triggering the flood in southern Alberta. However, given the enormity of the 2013 event and the need to better understand it to improve the prediction of such events, the objective of this work is to study the hydrometeorological factors that led to the flooding, as well as to provide a climatological view of the storm system.…”
Section: Introductionmentioning
confidence: 99%
“…Given the distinct seasonal differences in the study region's present and projected climate, results are organized largely by seasonal change. In addition, it is well-known that the climate of the region is strongly influenced by teleconnection patterns, particularly the Pacific North American (PNA) pattern (Wallace and Gutzler, 1981) during the cold season (see for example, Table 2 of Szeto, 2008), and quasi-stationary upper air circulation features over the northwestern U.S. during the warm season (Shabbar et al, 2011;Szeto et al, 2016). Emphases are thus placed on the analysis of future changes of such large-scale 5 circulation features.…”
Section: Model Datasets and Analysismentioning
confidence: 99%